Analysis of the Community's Role in Improving the Performance of Drainage Channels in Urban Areas - Apis Indica Adam; Ade Jaya Saputra (LEADER: Civil Engineering and Architecture Journal, 2023)
This research, employing a literature review methodology, critically examines the pivotal role of community engagement in enhancing the efficacy of drainage channels within urban landscapes. As urbanization accelerates, the imperative for effective stormwater management to avert flooding and environmental degradation becomes increasingly apparent. The study synthesizes existing scholarly works to discern patterns and insights regarding the impact of community involvement on the performance of drainage systems. Key objectives involve investigating community awareness, understanding local knowledge pertaining to drainage challenges, and evaluating the outcomes of community-driven initiatives. By drawing on diverse literature sources, this research aims to provide a comprehensive overview of the factors influencing successful community participation and the barriers impeding such engagement. The findings derived from this literature-centric approach contribute nuanced perspectives to the discourse, informing urban planners and policymakers about evidence-based strategies to leverage community involvement for resilient and sustainable urban drainage systems.